Quick response, a review of emergency remote education through the UPIS online classes in AY 2020-2021 - Denorte, Leopoldo R.
A case study of the UPIS Grade 4 first ever online art class, at the onset of the pandemic. The study aims to provide us with the scenario of the educational system during the recent COVID-19 pandemic. This paper focused on the emergent educational attempt as part of the Philippines' Emergency Response Education Program, which is the country's response to the global crisis.